STUDENTS’ ABILITY IN PRONOUNCING ENGLISH DIPHTHONGS - Dewi, Ni Luh Desy Suari; Utami, Gek Wulan Novi; Wardhana, I Gede Neil Prajamukti (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTPronouncing English vowels are more difficult than Indonesian vowels. English has more vowelsthan the Indonesian language. The difference between those vowels triggers some errors inpronouncing the English Vowel sounds made by Indonesian students. Therefore, in this research,the ability of second semester students of English Literature Study Program at Undhira Universityin pronouncing English vowels, especially diphthongs will be analyzed. The data were collectedby asking the students to make a video of pronouncing some words that consist of diphthongssounds. Based on the analysis, it can be concluded that students’ pronunciation is in the averagelevel to very good level. The most difficult diphthong to be pronounced is diphthong [ʊə] and theeasiest diphthong sound that can be pronounced is diphthong [ɔɪ].Keywords: Pronunciation, English Vowels, DiphthongsABSTRAKMengucapkan vokal bahasa Inggris lebih sulit daripada vokal bahasa Indonesia. Bahasa Inggrismemiliki lebih banyak vokal daripada bahasa Indonesia. Perbedaan antara vokal tersebut memicubeberapa kesalahan dalam melafalkan bunyi Vokal Bahasa Inggris yang dibuat oleh siswaIndonesia. Oleh karena itu, dalam penelitian ini akan dianalisis kemampuan mahasiswa SastraInggris semester II Universitas Undhira dalam melafalkan vokal bahasa Inggris khususnyadiftong. Pengumpulan data dilakukan dengan cara meminta siswa membuat video pengucapanbeberapa kata yang terdiri dari bunyi diftong. Berdasarkan analisis, dapat disimpulkan bahwapengucapan siswa berada pada level cukup hingga level sangat baik. Diftong yang paling sulitdiucapkan adalah diftong [ʊə] dan bunyi diftong yang paling mudah diucapkan adalah diftong[ɔɪ].Kata kunci: Pengucapan, Vokal Bahasa Inggris, Diftong